Size-resolved hygroscopicity and volatility properties of ambient urban aerosol particles measured by a volatility hygroscopicity tandem differential mobility analyzer system in Beijing - Yu, Aoyuan; Shen, Xiaojing; Ma, Qianli; Lu, Jiayuan; Hu, Xinyao; Zhang, Yangmei; Liu, Quan; Liang, Linlin; Liu, Lei; Liu, Shuo; Tong, Hongfei; Che, Huizheng; et al. (Atmospheric chemistry and physics, 2025)
The hygroscopicity and volatility of submicron ambient aerosol particles with diameters of 50, 80, 110, and 150 nm and the hygroscopicity of their non-volatile cores were measured using a volatility hygroscopicity tandem differential mobility analyzer (VH-TDMA) system at a relative humidity of 90 % and a thermal denuder temperature of 270 °C from 11 October to 6 November 2023 in Beijing. The mean hygroscopic growth factor (HGF) for particles of 50, 80, 100, and 150 nm diameter was 1.15 ± 0.07, 1.24 ± 0.08, 1.30 ± 0.09, and 1.36 ± 0.10, respectively, while the mean volatile shrink factor (VSF) was 0.51 ± 0.05, 0.55 ± 0.04, 0.56 ± 0.05, and 0.56 ± 0.07, respectively. Both the HGF probability density function (HGF PDF) and the VSF probability density function (VSF PDF) for all selected particle sizes exhibited a pronounced bimodal distribution, indicating that the particles were primarily in an external mixing state. Hygroscopicity was observed to increase with particle size in both clean and pollution periods, while volatility decreased slightly with particle size during the clean period, without an apparent trend during the pollution period. A positive correlation was identified between hygroscopicity and volatility, as well as between the number fraction of nearly hydrophobic (NH) and non-volatile (NV) particles. Furthermore, this study measured the HGF of the non-volatile core (HGFcore) of submicron ambient aerosol particles heated at 270 °C and derived the HGF of the volatile coating (HGFcoating). The mean HGFcoating for particles of 50, 80, 100, and 150 nm diameter was 1.17 ± 0.08, 1.27 ± 0.10, 1.35 ± 0.10, and 1.41 ± 0.10, respectively, which is 2 % to 7 % higher than the mean HGF for the same particle sizes. The mean HGFcore for particles of 50, 80, 100, and 150 nm diameter was 1.08 ± 0.03, 1.07 ± 0.03, 1.07 ± 0.03, and 1.09 ± 0.04, respectively. The HGFcore values were increased when the air mass passed over or originated from the Bohai Sea.